Dynamic relationship between green bonds, energy prices, geopolitical risk, and disaggregated level CO2 emissions: evidence from the globe by novel WLMC approach - Kartal, Mustafa Tevfik; Taskin, Dilvin; Depren, Serpil Kilic (SPRINGER, 2024)
This research analyzes the dynamic relationship between green bonds, energy prices, geopolitical risk, and CO2 emissions. In doing so, the study examines the global scale at disaggregated (i.e., sectoral) level, applies a novel time and frequency-based approach (i.e., wavelet local multiple correlation-WLMC), and uses high-frequency daily data between 1st January 2020 and 28th April 2023. In doing so, the study considers the potential differences among sectors. So, aggregated and disaggregated level CO2 emissions on sectoral bases are investigated. Hence, the study comprehensively uncovers the effect of the aforementioned indicators on global CO2 emissions. The results reveal that on CO2 emissions (i) the most influential factor is the geopolitical risk (2020/1-2021/5), green bonds (2021/5-2021/7), energy prices (2021/7-2023/1), and green bonds (2023/1-2023/4); (ii) the effects of the influential factors are much weaker (stronger) at lower (higher) frequencies; (iii) the effect of the influential factors change based on times and frequencies; (iv) however, the effects of the influential factors on CO2 emissions do not differ at aggregated or disaggregated levels. Overall, the results present novel insights for time and frequency-varying effects as well as both aggregated and disaggregated level analyses of global CO(2 )emissions.
Keywords: Green Bonds; Energy Prices; Geopolitical Risk; Global CO2 Emissions; WLMC; ECONOMIC-GROWTH; CLIMATE-CHANGE; OIL PRICE; CONSUMPTION; REGRESSION; IMPACT; Environmental Sciences & Ecology